Capacity development programmes for school governing bodies in Zimbabwe. - Makanani, Isaac (My University, 2016)
This study explored the role of capacity development programmes in the functioning of school governing bodies in Zimbabwe (statutorily referred to as School Development Committees - SDCs) with the Pafiwa circuit in Mutasa District of Manicaland Province as a study area. It sought to understand the types of capacity development programmes organised for SDCs and explored the effect these programmes had in the opinions of the recipients. The study is underpinned on a conceptual assumption that there is a link between the performance of SDCs and capacity development. The study revealed that SDCs in Pafiwa found capacity building programmes helpful, sustainable and to a large extent adding value to the performance of their SDCs. The findings confirmed that the real outcomes of capacity building are those that appeal to the recipients of such capacity. The study however acknowledges that there were other factors which were equally important in stimulating the effectiveness of SDCs. In Pafiwa, such factors include the use of a credible currency such as the United States Dollar which hedged the schools against high levels of inflation making it easy for schools to get transactional value for their money, an improved operating economic and political environment and most importantly improved school management skills by School Heads and Administrators resulting from multiple distance education programmes available to school managers in Zimbabwe such as the Zimbabwe Open University. The Pafiwa area has been used in this case to argue that capacity building stimulates effectiveness in education decentralisation provided the recipients find value in it.
MM
Keywords: School management and organization -- Zimbabwe. Educational change -- Zimbabwe.